The Management Team and Archival Appraisal - Lambert, James (Archivaria, 2005)
In appraising documents, the archivist must aim for a “just” selection of an institution’s recorded information. In Edgar Morin’s words, this means a selection which makes the link between “precision,” “fairness,” a document’s “dying a natural death,” and its “being forever forgotten due to cultural selection.” Since an institution can be conceived, built, and perceived in different ways, selection of information should be able to mirror these different views of reality. It is only by a “just” selection of the institution’s recorded information that the management of the institution can find in its archives the “meaningful vestiges” which give a sense to current reality and which inform the road to the future. RÉSUMÉ L’évaluation des documents par l’archiviste doit viser une sélection « juste » de l’information organique et consignée, c’est-à-dire, une sélection qui fait correspondre « la justesse » et « la justice », « la mort naturelle » des documents et « l’oubli qu’impose la sélection culturelle », pour employer des termes d’Edgar Morin. L’organisme étant un phénomène qui peut être conçu, bâti et perçu de différentes manières, une sélection « juste » de l’information doit constituer un miroir de l’organisme « modulable » aux différentes manières de le percevoir. C’est seulement grâce à une sélection juste de l’information organique et consignée que la direction d’un organisme pourra trouver dans les archives de celui-ci des « traces signifiantes », qui donnent un sens à l’actualité et permettent de clarifier les chemins de l’avenir.